2018
DOI: 10.3390/s18103301
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Number of Modes in Metasurfaced Reverberation Chambers for Field Uniformity Improvement

Abstract: The use of metasurfaces to increase the number of modes, lower the operating frequency, and improve the field uniformity in reverberation chambers (RCs) is investigated in this paper. The method used to improve the field uniformity and decrease the resonance frequencies is based on increasing the number of modes by using the concept of subwavelength cavities. The resonance frequencies of a RC with metasurface wall are derived and expressed analytically in terms of macroscopic characteristics. Simulation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…It can be noted that the selected number of experimental frequency points are much higher than the defined minimum limits of Table 1. It was done as the higher number of frequency/stirrer samples are recommended for the more accurate estimation of the field uniformity at low frequencies 8,18,25 . Figure 13 shows the actual picture of the experimental settings inside the RRA RC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be noted that the selected number of experimental frequency points are much higher than the defined minimum limits of Table 1. It was done as the higher number of frequency/stirrer samples are recommended for the more accurate estimation of the field uniformity at low frequencies 8,18,25 . Figure 13 shows the actual picture of the experimental settings inside the RRA RC.…”
Section: Methodsmentioning
confidence: 99%
“…It was done as the higher number of frequency/stirrer samples are recommended for the more accurate estimation of the field uniformity at low frequencies. 8,18,25 Figure 13 shows the actual picture of the experimental settings inside the RRA RC.…”
Section: Effect Of Stirrer Type On Rc Fieldmentioning
confidence: 99%
“…The procedure is applicable even for the case when more than one antennas are present in an RC. In (20), η o is the wave impedance, represents the permittivity of the RC propagation medium, and η depicts the efficiency of the antenna which can be estimated using (19). The term 1 − | S 11 | 2 in (20) also represents antenna efficiency (see 19).…”
Section: ) Frequency Domain Qmentioning
confidence: 99%
“…In (20), η o is the wave impedance, represents the permittivity of the RC propagation medium, and η depicts the efficiency of the antenna which can be estimated using (19). The term 1 − | S 11 | 2 in (20) also represents antenna efficiency (see 19). This simplifies (20) to (21).…”
Section: ) Frequency Domain Qmentioning
confidence: 99%
“…The main conclusion in [ 11 ] was that although the field uniformity was only somewhat improved for the MRC with the rotating 1-bit coding diffusion metasurface (as compared to the traditional one), an extended MRC test zone was achieved due to the lack of mechanical stirrer. In [ 13 ], we analyzed the physical mechanism for increasing the number of modes, lowering the operating frequency, and improving the field uniformity in the reverberation chambers, and concluded that a designed sequential metasurface provided better stirring effect than the random one. After dealing with these studies, it is concluded that the coding metasurface stirrer can improve the uniformity of field distribution in the MRC, and can replace the traditional metallic stirrer.…”
Section: Introductionmentioning
confidence: 99%